Valorization of animal waste from aquaculture through composting: Nutrient recovery and nitrogen mineralization - Lopes, Ivã Guidini [UNESP]; Braos, Lucas Boscov [UNESP]; Cruz, Mara Cristina Pessôa [UNESP]; Vidotti, Rose Meire [UNESP] (Elsevier, 2021)
Aquaculture production has been exponentially growing worldwide, which reflects in the generation of increasing amounts of waste materials. When poorly managed or disposed inadequately, aquaculture-derived wastes can compose social, economic and environmental issues. In this study, windrow composting was evaluated as a means of increasing the activity's sustainability through waste management, aiming to demonstrate a way of achieving circularity. For this purpose, four fish waste-based composts produced in an aquaculture research center were chemically evaluated and tested as soil amendment. The results indicated that harnessing wastes from aquaculture production is a valid and simple path to achieve circularity, as it is possible to convert waste into valuable, nutrient-rich composts that can be reintroduced in new productive processes, such as agriculture, in replacement of chemical fertilizers.
Keywords: Agriculture; Circular economy; Crop; Fish waste; Soil fertility; Sustainability